2015
DOI: 10.1007/s00347-015-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von 20 % Schwefelhexafluorid (SF6) auf humane korneale Endothelzellen

Abstract: The use of SF6 20 % as tamponade in the anterior chamber for posterior lamellar keratoplasty can be proposed as a safe alternative to pure air filling related to endothelial cell loss. Increased toxic effects on the corneal endothelium by SF6 20 % were not detected in this study; however, further prospective clinical trials are needed to examine the long-term effects in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although the gas is thought to be inert, increased buoyancy and longevity of the gas may have mechanical effects on the endothelial surface (13) . A recent in vitro study, however, found no significant difference between SF 6 and air on endothelial cell counts or toxicity of corneal endothelial cells (14) . Additionally, Guell et al found no difference in endothelial cell counts between use of SF 6 or air ≤3years after DMEK (9) .…”
Section: Discussionmentioning
confidence: 82%
“…Although the gas is thought to be inert, increased buoyancy and longevity of the gas may have mechanical effects on the endothelial surface (13) . A recent in vitro study, however, found no significant difference between SF 6 and air on endothelial cell counts or toxicity of corneal endothelial cells (14) . Additionally, Guell et al found no difference in endothelial cell counts between use of SF 6 or air ≤3years after DMEK (9) .…”
Section: Discussionmentioning
confidence: 82%